2016
DOI: 10.1111/vde.12400
|View full text |Cite
|
Sign up to set email alerts
|

Use of mycophenolate mofetil to treat immune‐mediated skin disease in 14 dogs – a retrospective evaluation

Abstract: This study supports the use of MMF as a second-line immunotherapeutic in immune-mediated skin disease in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 18 publications
1
64
0
2
Order By: Relevance
“…Recommended starting dosages for mycophenolate mofetil in dogs have varied from 10 to 20 mg/kg PO q12h, but gastrointestinal signs at the higher end of the dosage range often will necessitate dose reductions. Reported prevalence of diarrhea can be ≥20%, and may be delayed for 1‐2 weeks after starting treatment . Generally, starting dosages of 7‐10 mg/kg PO q12h (14‐20 mg/kg total daily dose) are associated with a much lower prevalence of diarrhea .…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Recommended starting dosages for mycophenolate mofetil in dogs have varied from 10 to 20 mg/kg PO q12h, but gastrointestinal signs at the higher end of the dosage range often will necessitate dose reductions. Reported prevalence of diarrhea can be ≥20%, and may be delayed for 1‐2 weeks after starting treatment . Generally, starting dosages of 7‐10 mg/kg PO q12h (14‐20 mg/kg total daily dose) are associated with a much lower prevalence of diarrhea .…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…In cats and dogs, the disposition of MPA seems to be highly variable (Ackermann et al., ; Slovak, Rivera, et al., ), as reported in humans (Le Meur et al., ; Zabotti et al., ; Mok, ). Variability in drug disposition of MPA could result in unpredictable safety and efficacy and explain interindividual variability in drug tolerance (Streicher et al., ; Martial et al., ; Filler, Alvarez‐Elías, McIntyre, & Medeiros, ; Zhang & Chow, ).…”
Section: Introductionmentioning
confidence: 94%
“…The prodrug mycophenolate mofetil (MMF) has been shown to be a promising drug for the treatment of autoimmune diseases in dogs and cats (Ackermann, May, & Frank, 2017;Bacek & Macintire, 2011;Machka et al, 2014;Segev, Cowgill, Heiene, Labato, & Polzin, 2013;Yau & Bianco, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycophenolate mofetil is the prodrug of mycophenolic acid (MPA); MPA is a potent and reversible inhibitor of de novo purine biosynthesis required for T and B lymphocyte proliferation . A retrospective study reported successful usage of oral MMP in several immune‐mediated skin diseases in dogs; the primary adverse effects involved gastrointestinal signs, diarrhoea and vomiting . Diarrhoea was observed in our case at the initial high MMF dosage and resolved by halving the daily MMF dose.…”
Section: Discussionmentioning
confidence: 78%